Household food insecurity is associated with respiratory infections among 6-11-month old infants in Rural Ghana - Ohemeng, A.; Marquis, G.S.; Lartey, A. (Pediatric Infectious Disease Journal, 2015)
Background: To determine the relationship between household food insecurity (HHFI) and symptoms of respiratory infections among infants in rural Ghana. Methods: The study was cross-sectional. The outcome variables were symptoms of respiratory infections (cough and nasal discharge) in infants. HHFI was measured using a 15-item modified U.S. Department of Agriculture (USDA) household food security module. Households were classified as food insecure if they had an affirmative answer for at least 1 item. Associations were examined using multiple logistic regression analysis. Data were collected in 32 communities located in 3 rural subdistricts in the Upper Manya Krobo district of the Eastern region of Ghana. The sample included 367 infants aged 6-11 months who attended a community-based growth monitoring session. Results: Overall, 20.5% of households reported experiencing food insecurity in the last month. Compared with infants in food secure households, infants living in food insecure households were about twice as likely to experience cough (adjusted odds ratio: 2.25, 95% confidence intervals: 1.25, 4.04) and nasal discharge (adjusted odds ratio: 1.87, 95% confidence intervals: 1.05, 3.36). Conclusion: Infants living in food insecure households are at an increased risk of respiratory tract morbidity. Interventions that address HHFI might be important to improve infant health in rural Ghana. © 2015 Wolters Kluwer Health, Inc.
Keywords: Ghana; household food insecurity; infants; respiratory infections